Knowledge, attitude, and practice towards evidence-based medicine among hospital physicians in Qassim Region, Saudi Arabia - Alshehri, Abdussalam Ali; Al-Khowailed, Mohammad Saleh; Alnuaymah, Fahad Mohammed; Alharbi, Asma Sameer; Alromaihi, Meaad Saif; Alghofaili, Ruba Saleh; Al-Maddallah, Wala’a Saleh; Alqattan, Selma Jawad; Alyahya, Maytha Abdullah (International Journal of Health Sciences, 2018)
Objectives: To determine the knowledge, attitude and practice regarding evidence based medicine (EBM) among hospital physicians in Qassim region of Saudi Arabia. Methods: It is a cross-sectional study. A self-administered questionnaire survey was done among 288 physicians working in secondary and tertiary care centers. The study was carried out between June and September 2015. Results: The overall response rate for the survey was 72%. Majority of the respondents had a positive attitude toward EBM and welcomed the concept. A total of 83% respondents stated that they used EBM in their daily practice and 93.5% agreed that practicing EBM improves patient care. There was a moderate level of awareness regarding extracting information from journals and clinical evidence databases. Although the respondents were aware and demonstrated familiarity with the process of knowledge extraction procedures to determine the best care, as many as 40% did not use them. The respondents had a poor overall understanding of the technical terms used in EBM. Among the respondents, 38.5% thought that the best way to move from opinion-based medicine to EBM was through learning the skills of EBM. The factors that positively affected physician awareness included: academic qualification and professional title. Knowledge and attitude were affected by qualification, professional title and specialty. Conclusion: The attitude of most physician practitioners in this study is favorable towards EBM, but this was not correlated with knowledge and awareness. The inclusion of physician training courses in EBM concepts, technical terms and applied practice is highly recommended.